2002
DOI: 10.1136/gut.50.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of adjuvant therapy for hepatocellular carcinoma during the waiting list for liver transplantation

Abstract: Background: Survival after liver transplantation for early hepatocellular carcinoma (HCC) is worsened by the increasing dropout rate while waiting for a donor. Aims: To assess the cost effectiveness of adjuvant therapy while waiting for liver transplantation in HCC patients. Method: Using a Markov model, a hypothetical cohort of cirrhotic patients with early HCC was considered for: (1) adjuvant treatment-resection was limited to Child-Pugh's A patients with single tumours, and percutaneous treatment was consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(205 citation statements)
references
References 36 publications
4
194
1
6
Order By: Relevance
“…243 Increasingly, techniques such as those described above are being used with the aim of delaying tumour progression in patients awaiting OLT (neoadjuvant or bridging therapy). 244 This approach has not been assessed in any randomised trials; however, some observational [245][246][247][248] and modelling 228,249 studies have suggested that it may assist in waiting list management, thereby maximising the effectiveness of an OLT programme. It has been emphasised that, although bridging strategies may induce objectively demonstrable pretransplant tumour control, this apparent effectiveness may not ultimately be reflected in survival benefit following OLT.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…243 Increasingly, techniques such as those described above are being used with the aim of delaying tumour progression in patients awaiting OLT (neoadjuvant or bridging therapy). 244 This approach has not been assessed in any randomised trials; however, some observational [245][246][247][248] and modelling 228,249 studies have suggested that it may assist in waiting list management, thereby maximising the effectiveness of an OLT programme. It has been emphasised that, although bridging strategies may induce objectively demonstrable pretransplant tumour control, this apparent effectiveness may not ultimately be reflected in survival benefit following OLT.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…20 Two decision analysis studies found a treatment advantage based on the waiting time and the type of treatment. 21,22 The first study (from the BCLC group) 21 compared resection, percutaneous ethanol injection (PEI), and no treatment in a scenario in which the dropout rate without treatment was 10% at 22 analyzed TACE versus no treatment in T2 patients and assumed a TACE response rate of 30% and a tumor progression rate of 7% per month. The TACE treatment had a statistical benefit at the waitlist time breakpoints of 4 and 9 months (P < 0.05).…”
Section: Studies Comparing the Dropout Rates Of Treated And Untreatedmentioning
confidence: 99%
“…31 Liver resection was considered only in Childs-Pugh A patients while percutaneous treatment was considered for B patients as well. Surgical resection increased the transplantation rate by more than 10% and increased the life-expectancy by 4.8-6.1 months at a cost of $40,000/-per life year gained if the waiting time was more than 1 year.…”
Section: Down-staging For Liver Transplantmentioning
confidence: 99%